Teaching as career choice as perceived by technical and vocational education student teachers - Ismail, Normala (2013)
There is at present an interesting debate on student teachers choosing teaching as a career specifically on the choices or factors that persuade them into doing so. Student teachers have the option during their education program whether or not to choose teaching as a career. The motivating factors which include perception, expectation and satisfaction significantly contribute in the decision making of student teachers in choosing teaching or other professions. The factors that influence their decision to choose teaching as a career will have a noteworthy impact on the duration of their stay in the profession. The purpose of this research is to investigate the factors as perceived by Technical and Vocational Education (TVE) student teachers that led them to choose the teaching as career. This is a quantitative research and to gather the necessary data, a survey was carried out covering 300 final-semester TVE student teachers from four public university institutions in Malaysia. The questionnaire administered to the respondents, was adopted and adapted from the Factor Influencing Teaching-Choice “FIT- Choice Scale” and focused on the student teacher’s motivation factors namely intrinsic, extrinsic, and altruistic, perception,expectation and satisfaction with regard to teaching career. The data was analysed using descriptive statistics and inferential statistics. The results indicated that for a majority of the respondents, the level of all motivating factors inducing them towards the teaching career including the intrinsic motivation, extrinsic motivation, altruistic motivation and satisfaction are generally high. In addition, the majority of the respondents had positive perceptions and expectation about the teaching career. There was no significant difference between gender and teaching as a career choice among TVE student teachers, [χ2 = .153, df= 1, n = 300, p >.005]. The chi- square analysis also indicates that there was no significant difference between academic program followed and teaching as a career, [χ2 = 7.661, df= 5, n = 300, p > .005]. In particular, dicriminant analysis revealed that Wilk’s Lamda was significant [h = .73, h2= 61.672, p < .001] and majority of respondents who intended to pursue a teaching career mentioned that motivational factors namely, intrinsic, extrinsic and altruistic are the most popular combination of choices that best distinguish students who choose teaching from those who do not. The perceptions variables did not contribute strongly to the discriminant function yet it is moderately highly (negatively) correlated with the overall discriminant function. In conclusion, this research can contribute vastly to strategies of recruitment and retention of teachers in the teaching profession.